Taxonomia e potencial antimicrobiano de fungos depositados no acervo de pesquisa da Central de Recursos Microbianos da UNESP - Polezel, Danilo Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Culture collections are keystones in the preservation, cataloging and exploration of microbial diversity. In order to meet international standards of deposit and supply of biological materials, the UNESP-Microbial Resources Center (CRM-UNESP) started their suitability for functioning and management to reach international standards; which include taxonomic authentication of cultures preserved in the collection. Using an adapted molecular screening protocol (microsatellites) coupled with morphological and molecular markers, we obtained the taxonomic identification of 189 out of 201 filamentous fungi from the CRM-UNESP research collection. In order to gather information on the biotechnological potential of these isolates, we also evaluated the production of antimicrobial compounds. After revival and purification of fungal isolates, we identified 66 genera and 116 species; comprehending the most abundant genera: Fusarium (18.9%), Clonostachys (11.4%), Trichoderma (7%) and Penicillium (6.5%). All isolates were evaluated for the production of secondary metabolites with antibacterial and antifungal properties, according to a high-throughput method (also adapted in this study), towards agricultural (Xanthomonas citri subsp. citri) and clinical-relevant (Staphylococcus aureus, Escherichia coli, Candida albicans, Candida krusei and Candida parapsilosis) reference strains. The majority of culture broths (62.7%) showed antagonist activity against at least one of the reference strains. Culture broths of Penicillium aurantiogriseum LESF 194, Clonostachys rosea LESF 389, Penicillium dodgei LESF 487, Xylaria sp. 4 LESF 502 and from the non-identified fungus LESF 227 inhibited the growth of all reference strains. Our results contributed for the establishment of two screening approaches in the routine of CRM-UNESP. These methods allowed the identification of the various fungal isolates examined as well as the evaluation of the antimicrobial potential of ...

As coleções de culturas são importantes pilares na preservação, catalogação e prospecção da biodiversidade microbiana. Com o propósito de atender ao depósito e fornecimento de material biológico de qualidade, a Central de Recursos Microbianos da UNESP (CRM-UNESP) iniciou sua adequação para alcançar os padrões internacionais de operação e gerenciamento; o que inclui a autenticação taxonômica das culturas mantidas na coleção. Utilizando um método de triagem molecular adaptado nesse estudo (microssatélites), aliado ao uso de marcadores morfológicos e moleculares, realizamos a identificação taxonômica de 189 isolados, de um total de 201 fungos filamentosos selecionados com base na diversidade de fontes de isolamento e mantidos no acervo de pesquisa da CRM-UNESP. Com o intuito de agregar informações sobre o potencial biotecnológico desses isolados, também avaliamos a produção de compostos antimicrobianos. Após a reativação e purificação dos isolados, foram identificados 66 gêneros e 116 espécies, sendo que os gêneros mais abundantes foram: Fusarium (18,9%), Clonostachys (11,4%), Trichoderma (7%) e Penicillium (6,5%). Todos os 201 isolados foram avaliados quanto à produção de metabólitos secundários com propriedade antibacteriana e antifúngica, segundo um método de alto desempenho (também adaptado neste estudo), frente a micro-organismos de interesse agrícola (Xanthomonas citri subsp. citri) e clínico (Staphylococcus aureus, Escherichia coli, Candida albicans, Candida krusei e Candida parapsilosis). Do total dos cultivos brutos avaliados, a maioria (62,7%) apresentou atividade antagonista frente, a pelo menos, um dos micro-organismos de referência. Os cultivos brutos dos fungos Penicillium aurantiogriseum LESF 194, Clonostachys rosea LESF 389, Penicillium dodgei LESF 487, Xylaria sp. 4 LESF 502 e de um isolado não identificado LESF 227 inibiram o crescimento de todos os micro-organismos de...
Keywords: Micro-organismos; Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Biociências (Campus de Rio Claro) Central de Recursos Microbianos; Fungos; Microssatélites (Genética)